Aura dalam Reproduksi Digital: Membaca Ulang Walter Benjamin - Fransisco Budi Hardiman (Jurnal Ledalero, 2020)
Walter Benjamin’s essay, The Work of Art in the Age of Mechanical Reproduction (1939), has revealed the fundamental changes of modern work of art affected by its mechanical reproduction. Camera, tape recorder, print machine have turned the work of art to be mass consumption, autonomous from tradition and ritual, and it has now a political function. According to Benjamin all of those new technologies have faded up the aura since the work of art lost its authenticity and its uniqueness. We are in the different era than Benjamin’s because nowadays digital reproduction by means of the internet ends the need of medium for the work of art, multiply and spread it very rapidly. The author comments on Benjamin’s analysis and applies it to discuss the ontological, epistemological, and axiological issues of the work of art in the age of digital reproduction. He argues that in the digital age the work of art will be still auratic if it reveals ‘the extraordinary’ in the experience of our humanity. Key words: aura, hyperpolitization, work of art, medium, attention, digital reproduction